Exploring the educational needs of young adults with hearing disability, before the Taliban Regime in Kabul, Afghanistan: a phenomenological study - Amarkhail, Freba; Ibrahimkhil, Fahima; Sidek, Suriati (The University of Gondar, Ethiopia, 2024)
Purpose: The primary aim of the study was to explore the educational needs of young adults with hearing disability in pre-Taliban administered Kabul, Afghanistan. Method: A qualitative approach was utilised, specifically employing the phenomenological method. In-depth semi-structured interviews were conducted with ten participants, allowing them to articulate their experiences and perspectives in detail. Data was analysed thematically, following six key steps. Results: The findings underscore the importance of facilitating a good quality educational system, employing qualified teachers, and ensuring the right to access better education for individuals with hearing disability. Addressing these fundamental components is crucial to providing a motivating and conducive learning environment, and enhancing educational opportunities to meet the unique educational needs of these individuals. Conclusion: Individuals with hearing disability face many challenges in Afghanistan’s education system. Despite commendable initiatives, the government’s neglect and financial constraints hinder optimal development. Two proposed approaches — special education and inclusive education — highlight potential solutions, emphasising the need for teacher training and a supportive learning environment. The study also advocates for the universal right to quality education for individuals with hearing disability, calling for improved services and special classes tailored to their unique needs. However, the absence of data on individuals with hearing disability in Afghanistan, security concerns during data collection, and the unavailability of sign-language interpreters are some of the study’s limitations.